Development and Validation of an RP-HPLC Method for Gefitinib in Bulk and Pharmaceutical Dosage Forms using Central-Composite Design - Kiran Kumar Buralla (Journal of Global Pharma Technology, 2019)
Abstract:Objective: Development of an accurate, sensitive, precise, robust, economical and quick isocratic reverse-phase high-performance liquid chromatography (RP-HPLC) method complying quality by design (QbD) and authorize as per ICH guidelines for the quantitative evaluation of Gefitinib in bulk and pharmaceutical dosage form.Method: The simultaneous estimation of the Gefitinib with Sorafenib as an internal standard in bulk and pharmaceutical dosage forms by the assistance of chemometrics, multicriteria decision-making approach. The separation was accomplished by utilizing/with Phenomenex Enable C18 column (15x4.6mm, 5µm particle size); and PDA-UV detection set at 250nm was developed and validated Gefitinib in pure form as well as pharmaceutical formulation, optimized by utilizing/with Derringer’s desirability functions. The mobile phase used for the separation was a mixture of Acetonitrile and Phosphate buffer (30:70 %v/v) and the pH 3, which was adjusted with ortho-phosphoric acid, the flow rate was 1.6 ml/min.Result: Newly developed method resulted an elution time of the drug at 3.264 min. The regression coefficients (R2) were observed to be 0.999 for all models. The detection (LOD) and quantification limits were 10.47 mg/ml, and 31.74 mg/ml, respectively. The relative standard deviation was calculated as 0.4412%.Conclusion: Method developed and validated by determining its precision; accuracy; and system stability. The results of the study demonstrated that the planned RP-HPLC method is simple; rapid; precise; and accurate, which is helpful for the analysis of Gefitinib in bulk as well as pharmaceutical dosage forms.Keywords: Chemometrics, RP-HPLC, RSM, Tyrosine kinase inhibitors, Gefitinib, Sorafenib.1) Tripati KD. Essentials of medical pharmacology, 5th edition, 2003;769-770.2) Pao W, Miller V, Zakowski M. EGF receptor gene mutation are common in lung cancer from never smokers, and are associate with sensitivity of tumors to Gefitinib and Erlotinib. Proceedings of the national academy of science of the state of America. 2004;101(36):13306-11.3) Sordella R, Bell DW, Haber DA, Serttleman J. Gefitinib-sensitizing EGFR mutations in lung cancer activate anti-apoptotic pathways. Science. 2004;305(5687):1163-7.4) Takimoto CH, Calvo E. Principles of oncologic pharmacotheraphy, cancer management: A multidisciplinary approach, 11th edition. 2008.5) Siva Kumar R, Yogeshwara KR, Manish G, Nitesh K, Siva Ganesh, Jeenet J. Development and Validation of Stability Indicating HPLC Method for Gefitinib and Its Related Compounds and Characterisation of Degradation Impurities. J Pharm Drug Deliv Res. 2017;6(1):1-14.6) Indian pharmacopeia, 2, 2010;1484.7) The Merck index. 14th edition. 2006;851.8) Alagar Raja M, Joshna P, David B, Rao KNV, Selva Kumar D. Analytical method development and validation of Gefitinib (anti cancer drug) in pharmaceutical tablet dosage form by using RP-HPLC. Asian journal of pharmaceutical analysis and medical chemistry. 2014;2(3):127-133.9) Montgomery D. Design and analysis of experiment” New York, John Wiley and Sons. 1991. 10) Shiow-Ling L, Wen-Chang C, Enz. Microb. Technol. 1997;21:436. 11) Myers RH, Montgomery DC. Response Surface Methodology: Process and Product Optimization Using Designed Experiments, 2nd ed. Wiley, New York. 2002. 12) Ferreira SL, Bruns RE, Ferreira HS, Matos GD, David JM, Brandao GC, da Silva EG, Portugal LA, dos Reis PS, Souza AS, dos Santos DS. Anal. Chim. Acta. 2007;597:179. 13) International Conference on Harmonization. ICH Q2 (R1). Validation of analytical procedures: text and methodology, ICH Secretariat, Geneva. 2005. 14) Bhatt DA, Rane SI. QbD approach to analytical RP- HPLC method development and its validation. Int. J. Pharm. Pharm. Sci. 2011;3:1179–1187. 15) Bhutani H, Kurmi M, Singh S, Beg S, Singh B. Quality by design (QbD) in analytical sciences: an overview, Pharm. Times. 2014;46:71–75. 16) Schmidt AH, Stanic M, Molnar I. In silico robustness testing of a compendial HPLC purity method by using a multidimensional design space build by chromatography modeling- case study pramipexole. J. Pharm. Biomed. Anal. 2014;91:97–107. 17) Sarwar B, Kanchan K, Suryakanta S, and Saquib Hasnain M. Development and validation of RP-HPLC method for quantification of Amoxicillin tryhydrate in bulk and pharmaceutical formulations using Box-Behnken experimental design. Journal of Liquid Chromatography & Related Technologies. 2012;35:393-406.18) Chaudhari SR, Shirkhedar AA. Design of experiment avenue for development and validation of RP-HPLC-PDA method for determination of apremilast in bulk and in-house tablet formulation, Journal of Analytical Science and Technology. 2019;10:10. 19) ICH, ICH Draft Guidelines on Validation of Analytical Procedures: Definition and Terminology, Switzerland, Federal Register, IFPMA. 1995.20) Ajaz A, Mohammad R, Khalid MA, Kazi M, Faiyaz S. Box-Behnken supported development and validation of robust RP-HPLC method: An application in estimation of pravastatin in bulk and pharmaceutical dosage form. 2016;61(2):2963-2967. 21) Padmaja N, Veerabhadram G. Development and validation of analytical method for Simultaneous estimation of Empagliflozin and Linagliptin in bulk drugs and combined dosage forms using UV-visible spectroscopy. Der Pharmacia Lettre. 2015;7:306-312.22) Beg S, Kohli K, Swain S, Hasnain MS. Development and validation of RP-HPLC method for quantitation of amoxicillin trihydrate in bulk and pharmaceutical formulations using Box-Behnken experimental design. Journal of Liquid Chromatography and Related Technologies. 2011;35:393–406.23) Barmpalexis P, Kanaze FI, Georgarakis E. Developing an optimizing a validated isocratic reversed phase HPLC separation of nimodipine and impurities in tablet using experimental design methodology. Journal of Pharmaceutical and Biomedical Analysis. 2009;49:1192-1202.24) Suresh R, Manavalan R, Valliappan K. Chemometrics Assisted RP- HPLC Method for the Simultaneous Determination of Levocetirizine, Ambroxol, and Montelukast in Pharmaceutical Formulation International Journal of Pharmaceutical and Chemical Sciences. 2012;1:1205-1220.25) Sujan B, MasudKaisar Md, Salim Hossain Md. Development and Validation of a Simple and Rapid UV Spectrophotometer Method for Assay of Linagliptin in Bulk and Marketed Dosage Form. Indian Journal of Novel Drug Delivery. 2013;5:221-224.26) Sara SM, Eman IE, Dalia AH, Magda AB. Stability- Indicating HPLC-DAD Method for the Determination of Linagliptin in Tablet Dosage Form: Application to Degradation Kinetics. Journal of Chromatographic Science. 2016;54:1560–1566.